The best seat in the house: investigating the emergence of livecasting in the UK - Cerski, Helena (2017)
The purpose of this dissertation is to investigate how livecasting - the use of cinemas to display a variety of live and recorded entertainment such as opera, theatre and ballet - has emerged in the UK between the years 2003-2016. In research approach, it draws on the development of primary case studies and secondary analyses of existing industry reports and literature regarding livecasting.